El problema teológico político La recepción de la Filosofía Política de Thomas Hobbes en la obra de Leo Strauss - Pierpauli), José Ricardo (Alpha Omega, 2013)
The present study aims to demonstrate that underlying the postulate in favour of natural law in the systematic work of Leo Strauss, his true position lies hidden, entirely autonomous from religion and from Supernatural Theology. The entire Political Philosophy of Strauss represents the drama of a constant tension to free philosophy, both from its weakening position from within Supernatural Theology and religious Faith, and from the immanence and relativism that threaten it from Historicism.